THE USE OF GRAPHIC ORGANIZERS IN TEACHING ENGLISH VOCABULARY - Koyshekenova, T.; Yakupova, K. (FAN va JAMIYAT, 2017)
The article is devoted to the investigation of the effectiveness of graphic organizers in teaching English vocabulary. Graphic organizers help in organizing information, on a list of paper (or on the screen of a computer) to improve remembering, learning, analyzing and using.